ENHANCING STUDENTS’ LEARNING ACTIVITY AND ACHIEVEMENT IN THE INVERTEBRATE SUBTOPIC THROUGH LABORATORY WORK - Lubis, Shofia; Gultom, Rahmad; Hasruddin (Jurnal Pelita Pendidikan, 2025)
The objectives of this study were to find out and knowing the effect of laboratory work on students’ learning activity and learning achievement on the topic of annelids and molluscs. This study was classified as quasi experimental with two group pretest – posttest design. This study was implemented at MAN 1 Medan grade X; samples of this study determined by cluster random sampling and obtained X-7 as experimental class and X-6 as control class. The study variable were consist of dependent variable, they are students’ learning activity and students’ achievement while the independent variable were using practicum method in experimental class and traditional method in control class. This study used test and non test instrument. Test instrument was cognitive test in form of multiple choice and essay whereas non test using observation sheet. The data analysis method was using t-test. The study result shows that involvement level of students’ learning activity on experimental class was higher than control class (62%> 45%). It means students’ learning activity in learning invertebrate subtopic that taught by practicum method more active than taught by traditional method. Average score of students’ achievements on experimental class was 83 (increase 34.17 point from pretest) and control class was 71.5 (increase 22.33 point from pretest). There was a significant difference between students’ achievement mean score on experimental class and control class then laboratory work have positive effect on students’ learning achievement in learning invertebrate subtopic at MAN 1 Medan.